Evaluation and Retest of Solar-Powered Thermoelectric Power Generator (Prototype α) - PANIGORAN HUTASUHUT (NIM : 13113064), ABDURRAHMAN
Prototype α is a solar-powered generator that has been designed, built, and tested to know the potency of the power generation of thermoelectric cooler [1]. From the result of the first test, the avarage power value is 0,44 mW, the maximum power is 2,4 mW, and the thermal efficiency is 0.042%. The result was relatively small compared to the theoritic value that had been calculated from the design. Beside that, it was known that the value of internal resistance (Ri) changed from time to time during the test. In this report, an evaluation of the previous test procedure was performed as the basis for designing the new test procedure. Next, a series of tests to determine the power generation potential of Prototype α was conducted using the new test procedure. The test series included internal resistance of multimeter testing, Seebeck coefficient of thermoelectric module testing, internal resistance of thermoelectric testing, and performance testing of Prototype α. The results of the evaluation indicated that the internal resistance of multimeter could influence the measurement result of the output voltage and output current from thermoelectric module. The results of the retest showed that the internal resistance and Seebeck coefficients were 4.6 Ω and 0.0383V / Ã‚ÂºC respectively. The resulting power potential averaged at 6.1 mW and the maximum power reached 10.1 mW with an average thermal efficiency of 1.76%. There was also a relationship between environmental factors with the temperature of the system, collectorÃ‚Â’s temperature distribution, and the generated power.